Book Review: Aro Velmet, Pasteur’s Empire: Bacteriology & Politics in France, Its Colonies, & the World (New York: Oxford University Press, 2020), pp. xiv + 306, $78.00, hardback, ISBN: 9780190072827. - Thompson, C. Michele (Medical History, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0025727321000508/resource/name/firstPage-S0025727321000508a.jpg
Keywords: dept.his